Imperialism and Financialism. A Story of a Nexus (Revised and Expanded) - Shimshon Bichler; Jonathan Nitzan (The Bichler and Nitzan Archives, 2010)
Over the past century, Marxism has been radically transformed in line with circumstances and fashion. Theses that once looked solid have depreciated and fallen by the sideline; concepts that once were deemed crucial have been abandoned; slogans that once sounded clear and meaningful have become fuzzy and ineffectual. But two key words seem to have survived the attrition and withstood the test of time: imperialism and financialism. Talk of imperialism and financialism – and particularly of the nexus between them – remains as catchy as ever. Marxists of different colours – from classical, to neo to post – find the two terms expedient, if not indispensable. Radical anarchists, conservative Stalinists and distinguished academics of various denominations all continue to use and debate them. The views of course differ greatly, but there is a common thread: for most Marxists, imperialism and financialism are prime causes of our worldly ills. Their nexus is said to explain capitalist development and underdevelopment; it underlies capitalist power and contradictions; and it drives capitalist globalization, its regional realignment and local dynamics. It is a fit-all logo for street demonstrators and a generic battle cry for armchair analysts. The secret behind this staying power is flexibility. Over the years, the concepts of imperialism and financialism have changed more or less beyond recognition, as a result of which the link between them nowadays connotes something totally different from what it meant a century ago. The purpose of our article is to outline this chameleon-like transformation, to assess what is left of the nexus and to ask whether this nexus is still worth keeping. In so doing, our goal is not to present our own view of the nexus, but rather to critique what others have written about it. We try to stick to the categories and units of the theories we examine – categories and units with which we often disagree – so that we can compare and contrast the theories on their own terms. And we make no attempt to pick and choose. We do not try to decide which version of the nexus is correct in some universal sense, and not even which version was correct for its time. Instead, our aim is to highlight the historical development of the nexus, particularly the loose manner in which it has been altered – to the point of meaning everything and nothing.
Keywords: 330; capital; dependency; finance; hegemony; imperialism; Marxism; monopoly; world systems